Five standards for effective teaching : how to succeed with all learners, grades K-8 - Dalton, Stephanie Stoll (San Francisco : Jossey-Bass, 2008)
"Five Standards for Effective Teaching offers teachers of grades K-8 system to support effective teaching, especially teaching through dialogue. Focusing on five essential pedagogy standards, the book describes teachers' implementations, 'best practice' strategies, and scores of classrooms activities. From research conducted by the Center For Research on Education, Diversity, and Excellence (CREDE), the five standards emphasize fundamentals underlaying effective teaching that lead to learning."--BOOK JACKET.
Includes bibliographical references
Keywords: Effective teaching -- United States; Teacher effectiveness -- United States